2006
DOI: 10.1159/000096522
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Colour Discrimination during the Menstrual Cycle

Abstract: A group of normal women of reproductive age were recruited to investigate colour discrimination during the various phases of the menstrual cycle. Colour vision was tested with the Farnsworth-Munsell 100-hue arrangement test, and the test was administered at 3 time points: the beginning of the cycle, ovulation, and the end of the cycle. We found that colour discrimination was better at ovulation than at the other 2 time points. It is possible that psychological as well as hormonal factors could contribute to im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…Rita et al (1981) found that a low dose (i.e., .005 mg.kg −1 ) of droperidol effectively treated PONV in children 11-15 years old undergoing puberty, but not in the 1 -5 and 6 -10 year old groups. Moreover, near ovulation, women tend to experience an increased sensitivity in auditory (Swanson & Dengerink, 1988), olfactory (Navarrete-Palacios et al, 2003), and visual (Eisner, Burke, & Tommey, 2004) including color vision (Giuffre, Rosa, & Fiorino, 2007) modalities, possibly exacerbating any mismatches between visual and vestibular perception. Given any putative effects of estrogen, it is still unclear as to why some studies find increased motion sickness and PONV near menses (e.g., Beattie et al, 1991;Golding et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Rita et al (1981) found that a low dose (i.e., .005 mg.kg −1 ) of droperidol effectively treated PONV in children 11-15 years old undergoing puberty, but not in the 1 -5 and 6 -10 year old groups. Moreover, near ovulation, women tend to experience an increased sensitivity in auditory (Swanson & Dengerink, 1988), olfactory (Navarrete-Palacios et al, 2003), and visual (Eisner, Burke, & Tommey, 2004) including color vision (Giuffre, Rosa, & Fiorino, 2007) modalities, possibly exacerbating any mismatches between visual and vestibular perception. Given any putative effects of estrogen, it is still unclear as to why some studies find increased motion sickness and PONV near menses (e.g., Beattie et al, 1991;Golding et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Aside from the well-documented sex differences in verbal, spatial, and perceptual motor tasks [3–6], sex differences and menstrual-cycle-related changes in basic measures of human sensory function have been reported for every major sensory system, including audition [7–9], vision [1014], olfaction (this review), gustation [1519], and the skin senses [2022]. Such effects, when present, are usually not large, raising the question as to what biological purpose they may serve.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggest that fluctuation in reproductive hormones, oestrogen and progesterone, during the ovarian cycle may influence cognitive function (Hampson, 2002), neural excitability (Smith et al, 2002) and some sensory processes, such as greater visual sensitivity (Eisner et al, 2004), better colour discrimination (Giuffre et al, 2007), a more sensitive sense of smell (Grillo et al, 2001) and lower pain thresholds (Bajaj et al, 2001) around the time of ovulation. Changes in auditory function during the ovarian cycle may also occur (Walpurger et al, 2004;Al-Mana et al, 2008).…”
Section: Introductionmentioning
confidence: 99%